Recent Advancement in Self Emulsifing Drug Delivery System - Bist, Vijay Laxmi; Faruk, Abdul (Journal for Research in Applied Sciences and Biotechnology, 2023)
Every day, researchers make new attempts to identify neurotherapeutics, but few of them make it to clinical trials. The main cause is their low bioavailability, which is connected to low water solubility, low permeability through biological membranes, and the hepatic first-pass metabolism. However, the most significant challenge in administering drugs to the brain is overcoming the blood-brain barrier. In order to get around it, intranasal administration has become more popular, sometimes even more so than oral administration. Because of its structure, the nasal cavity can bypass the blood-brain barrier and transport drugs to the brain directly. Nasal absorption increases the systemic bioavailability of highly processed substances because they bypass the hepatic first-pass metabolism. However, due to their unique physicochemical properties, most neurotherapeutics must be synthesized in lipidic nanosystems as self-emulsifying drug delivery systems (SEDDS). To load large quantities of lipophilic medicines into micro or nanoemulsions, these isotropic mixes of oils, surfactants, and co-surfactants are diluted in water. The goal of SEDDS is to increase the stability of labile pharmaceuticals against enzymatic activity, boost drug penetration through absorptive membranes, and reduce the likelihood of drug precipitation at absorption sites. Therefore, improved brain targeting and bioavailability of medications might be anticipated by combining the benefits of SEDDS with those of the intranasal route for brain delivery. In order to better understand the mechanisms involved in the intranasal administration of pharmaceuticals loaded in SEDDS, this paper provides a comprehensive characterization of SEDDS as a lipidic nanosystem. Finally, the in vivo effects of intranasal or oral delivery of SEDDS, showing their superiority over standard solutions or suspensions, are described.